Numerical solution of fuzzy differential equations using orthogonal polynomials. (2019) - Tapaswini, Smita; Chakraverty, Snehashish
The present paper proposed a new method to solve n th order fuzzy differential equations using collocation type of method. In the solution procedure, Gram Schmidt orthogonalisation process is used with Legendre and Chebyshev polynomials. Known example problems are solved and compared with the exact results to illustrate the efficiency and reliability of the proposed method.